“I am what i consume”: Exploring the interplay between identity and consumption among middle-class urban youths in Dhaka South City, Bangladesh - Arifur Rahaman; Debasish Kundu (Journal of Social Studies, 2025)
In the late modern era, identity is closely intertwined with consumption, shifting it from sustenance to a vital marker of individuality and a platform for showcasing fashion opulence in the social space. This study is an attempt to understand the mechanisms through which youth consumers shape their identities. Deploying a mixed-method approach, we gathered quantitative data through interviews administered by a semi-structured survey questionnaire. Complementing this, qualitative insights were gathered through in-depth interviews (IDI). Adopting a purposive sampling method frame, we interviewed 150 individuals (89 male, 61 female) from Dhanmondi, Dhaka, between March and April 2022. The objective was to unveil people’s attitudes, social norms, and behavioral influences shaping their intentions towards identity formation through consumption. Findings highlight that individuals’ attitudes and behavioral control serve as key predictors for their intention to mold a desired identity through consumption. The perception of one’s consumption as socially commendable, coupled with the approval of others, strongly influences this intention. In addition, perceived behavioral control emerged as a crucial predictor of the inclination to forge a desired identity. Notably, middle-class youths displayed a calculated and rational approach in their purchasing decisions, reflecting a strategic stance towards consumption. In-depth interviews show that social acceptance, identity expression, and feelings of fulfillment have significant effects on respondents' consumption practices, even though many oppose the idea that luxury consumption and mental well-being are positively associated. While shopping malls function as social and emotional spaces, people exhibit ambivalence, balancing desires for self-presentation and societal conformity with claims to independent selfhood. The study reveals that the late modern consumer society has ushered in changes conducive to conspicuous consumption. However, despite this trend, urban middle-class youths appear to align more with conventional consumer behaviour in many aspects. The pinnacle of conspicuous consumption has not yet been attained among this demographic, which suggests the evolving landscape in their consumption patterns.